Zeitschrift für Kristallographie - Crystalline Materials (Oldenbourg Wissenschaftsverlag, 1877)
Zeitschrift für Kristallographie - Crystalline Materials offers a place for researchers to present results of their crystallographic studies. The journal includes theoretical as well as experimental research. It publishes Original Papers, Letters and Review Articles in manifold areas of crystallography.